Answer: x = 7, x = -1
Step-by-step explanation: Move the term to the left side
x^2 + 2x - 7 = 8x
x^2 + 2x - 7 - 8x = 0
Combine like terms
x^2 + 2x - 7 - 8x = 0
x^2 - 6x - 7 = 0
x^2 - 6x - 7 = 0
a = 1
b = -6
c = -7
x = -(-6) + (-6)^2 - 4 x 1(-7)/ 2 x 1
Evaulate the Exponent
Multiply the numbers
Add the numbers
Evaluate the square root
Multiply the numbers x = 6 ± 8/2
To solve for the unknown variable, separate into two equations: one with a plus and the other with a minus.
x = 6 + 8/2
x = 6 - 8/2
Rearrange and isolate the variable to find each solution
x = 7
x = -1